Ionic Nanocomplexes of Hyaluronic Acid and Polyarginine to Form Solid Materials: A Green Methodology to Obtain Sponges with Biomedical Potential - María Gabriela Villamizar-Sarmiento; Ignacio Moreno-Villoslada; Samuel Martínez; Annesi Giacaman; Victor Miranda; Alejandra Vidal; Sandra L. Orellana; Miguel Concha; Francisca Pavicic; Judit G. Lisoni; Lisette Leyton; Felipe A. Oyarzun-Ampuero (Nanomaterials, 2019)
We report on the design, development, characterization, and a preliminary cellular evaluation of a novel solid material. This material is composed of low-molecular-weight hyaluronic acid (LMWHA) and polyarginine (PArg), which generate aqueous ionic nanocomplexes (INC) that are then freeze-dried to create the final product. Different ratios of LMWHA/PArg were selected to elaborate INC, the size and zeta potential of which ranged from 100 to 200 nm and +25 to −43 mV, respectively. Turbidimetry and nanoparticle concentration analyses demonstrated the high capacity of the INC to interact with increasing concentrations of LMWHA, improving the yield of production of the nanostructures. Interestingly, once the selected formulations of INC were freeze-dried, only those comprising a larger excess of LMWHA could form reproducible sponge formulations, as seen with the naked eye. This optical behavior was consistent with the scanning transmission electron microscopy (STEM) images, which showed a tendency of the particles to agglomerate when an excess of LMWHA was present. Mechanical characterization evidenced low stiffness in the materials, attributed to the low density and high porosity. A preliminary cellular evaluation in a fibroblast cell line (RMF-EG) evidenced the concentration range where swollen formulations did not affect cell proliferation (93−464 µM) at 24, 48, or 72 h. Considering that the reproducible sponge formulations were elaborated following inexpensive and non-contaminant methods and comprised bioactive components, we postulate them with potential for biomedical purposes. Additionally, this systematic study provides important information to design reproducible porous solid materials using ionic nanocomplexes.